Philanthropy in Vietnam - Dang Nguyen Anh; Le Kim Sa; Nghiem Thi Thuy; Nguyen Van Lang; Phi Hai Nam; Dang Nguyen Anh; Le Kim Sa; Nghiem Thi Thuy; Nguyen Van Lang; Phi Hai Nam (2011)
The Asia Foundation supported the Vietnam Asia Pacific Economic Center to carry out an initial research aimed at establishing a broad baseline regarding the state of philanthropic giving and activities in Vietnam. Examining both individual and corporate giving, the research draws out what do people give to, why do they give, and how do they give in order to identify potential and options to improve philanthropic giving and activities in Vietnam, from a more conducive policy environment to a more professionalized philanthropic sector.